Direct numerical simulation of the impact of a droplet onto a hot surface above the Leidenfrost temperature. (January 2017) - Rueda Villegas, Lucia; Tanguy, Sébastien; Castanet, Guillaume; Caballina, Ophélie; Lemoine, Fabrice
Highlights: Direct numerical simulations of Leidenfrost droplets. Dynamical effects and thermal effects in the vapor layer. Transition between evaporation and boiling. Accurate validations between numerical simulations and experiments. Abstract: In this paper, we compare numerical simulations and experiments on droplets impinging onto a hot surface at a temperature well above the Leidenfrost point, for different impacting Weber numbers ranging from 7 to 45. We use a novel numerical method for the simulation of two-phase flows with phase change (evaporation and boiling) which accounts for the heterogeneous thermodynamic conditions at the liquid/gas interface. We present the results of experimental and numerical values for the droplet shape, its spreading diameter and its loss of momentum. The numerical simulations determine the time-evolution of the average vapor layer thickness, which is typically from one to two orders of magnitude smaller than the initial droplet diameter. Thermal transfer between the liquid and the gas phases are also investigated both numerically and experimentally. In the numerical results, like in the experiments, the droplet heating increases with the impacting Weber numbers. The fully resolved direct numerical simulations allow for the accurate description of the multi-scale complex problem involving both fluid mechanics and coupled heat and mass transfer.